AIAA/AAS Astrodynamics Specialist Conference 2010
DOI: 10.2514/6.2010-7526
|View full text |Cite
|
Sign up to set email alerts
|

Entropy-Based Space Object Data Association Using an Adaptive Gaussian Sum Filter

Abstract: This paper shows an approach to improve the statistical validity of orbital estimates and uncertainties as well as a method of associating measurements with the correct resident space objects and classifying events in near realtime. The approach involves using an adaptive Gaussian mixture solution to the Fokker-Planck-Kolmogorov equation for its applicability to the resident space object tracking problem. The Fokker-Planck-Kolmogorov equation describes the time-evolution of the probability density function for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…More accurate filters which better approximate model nonlinearities and non-Gaussian PDFs are therefore sought. The Gaussian sum filter is one such example which has been investigated in SSA applications by the authors [2,3] and other researchers [4][5][6][7][8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More accurate filters which better approximate model nonlinearities and non-Gaussian PDFs are therefore sought. The Gaussian sum filter is one such example which has been investigated in SSA applications by the authors [2,3] and other researchers [4][5][6][7][8].…”
mentioning
confidence: 99%
“…Our philosophy is to not update the weights, which is justified because uncertainty consistency is achieved by working in coordinates adapted to the dynamics (i.e., orbital elements). On the other hand, some researchers [6][7][8] have proposed methods for adapting the weights based on various L 2 optimization criteria, for example, using the FPKE error as feedback. The impact of using one these weight update schemes during propagation is analyzed in this paper.…”
mentioning
confidence: 99%
“…However, there is not complete agreement on how the weights should be updated (if at all) following a prediction. Some researchers [11][12][13] have proposed online methods for adapting the weights based on various L 2 optimization criteria, for example, using the FPKE error as feedback. In another paper, 8 it was found that such weight update schemes do not improve uncertainty consistency when applied to the authors' GSF for the specific two-body problem in space surveillance.…”
Section: Features Of the Proposed Gaussian Sum Filtermentioning
confidence: 99%
“…The Gaussian sum filter is one such example which has been investigated in SSA applications by the authors 6-8 and other researchers. [9][10][11][12][13] The Gaussian sum filter (GSF) is based on a fundamental result of Alspach and Sorenson 9 which states that any PDF can be approximated arbitrarily close (in the L 1 sense) by a weighted sum (mixture) of Gaussian PDFs henceforth called a Gaussian sum. Thus, Gaussian sums provide a mechanism for modeling non-Gaussian densities and for more accurately approximating the solution of the Fokker-Planck-Kolmogorov equation 14 which governs the time evolution of a PDF under a nonlinear stochastic dynamical system.…”
Section: Introductionmentioning
confidence: 99%
“…The OD of RSOs can be carried out using many different types of estimation algorithms such as the batch least-squares [13], extended Kalman filter (EKF) [14], second-order Kalman filter [15], unscented Kalman filter [16], divided difference filter [17], Gaussian sum filter (GSF) [18], etc. Particle filtering (PF) [19,20], a Monte Carlo (MC)based method that requires the propagation of a large number of state estimates called particles, is theoretically one of the most accurate and robust, yet computationally intensive, filtering algorithms.…”
Section: Introductionmentioning
confidence: 99%